Risk Factors Analysis in Asphyxiated Newborn and Their Neurological Outcome in Relation to Hypoxic-Ischaemic Encephalopathy (Journal of Paediatric Surgeons of Bangladesh, 2015)
Background: Perinatal mortality rate in the developing world is still significantly higher than what obtained in the individualized nation1. Perinatal asphyxia has been established as one of the major causes of these deaths. Perinatal asphyxia is a serious clinical problem world wide. There are various reasons of failure to initiate and sustain breathing immediately after birth. Neurological complication like hypoxic ischaemic encephalopathy (HIE) following damage to the brain is very frequent and commonly seen in asphyxiated newborn .Objective: To find out the risk factors and the hospital outcome with special emphasis on HIE following perinatal asphyxia.Methods: It was a retrospective study on 92 (ninety two) consecutive cases of perinatal asphyxia admitted in the neonatal care unit of Sir Salimullah Medical College and Mitford Hospital during the period of January and February 2011.Results: The results revealed that during the study period the number of perinatal asphyxia in admitted in neonatal care unit was 92 out of 193 i.e. 47.6%. Out of 92 asphyxiated newborn 86% were admitted in first 24 hours of life. Among them 71% were inborn and of male sex. Most of them (69%) were of normal birth weight. Regarding gestational age 56% were term. Fifty one percent were delivered per vaginally. Majority of mothers (79%) received antenatal care. Intrapartum risk factors included premature rupture of membrane (PROM) 19%, prolonged labour 15%, pregnancy induced hypertension 13%, antepartum haemorrhage 13%, preeclampsia and eclampsia 10%, obstructed labour 10%, malpresentation 8%, multiple gestation 8%. 60% mothers had multiparity. Presenting complaints were respiratory distress characterized by tachypnea /chest indrawing (30%), grunting (25%), convulsion (21%), irritability or excessive crying (9%), poor feeding or sucking (8.6%). About neurological complications 45% developed hypoxic ischaemic encephalopathy. Out of 42 HIE cases 60% had grade II encephalopathy. Grade I HIE was found in 26% of cases and 14% cases had grade III or severe encephalopathy. About hospital outcome 58% had hospital stay for minimum 5 days and 63% were discharged after improvement Thirteen percent were discharged on risk bond. 22 cases died during hospitalizationConclusion & Recommendation: The rate of hospital admission of Perinatal asphyxia as well as Neurological complication like hypoxic ischemic encephalopathy (HIE) was very high though majority of mother received antenatal care and affected newborns were inborn. So proper attention and timely intervention as well as resuscitation of newborn delivered in the hospital is essential to prevent the unwanted neurological complication of Perinatal asphyxia like HIE as well as other morbidity and fatality.J. Paediatr. Surg. Bangladesh 4(2): 54-57, 2013 (July)